2020
DOI: 10.1016/j.ijid.2020.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of intestinal SARS-CoV-2 infection in patients with COVID-19 leads to re-admission after pneumonia resolved

Abstract: The current reports of COVID-19 focus on the respiratory system, however, intestinal infections caused by SARS-CoV-2 are also worthy of attention. This paper reported persistence of intestinal SARS-CoV-2 infection leads to re-admission after pneumonia resolved in three cases with COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 6 publications
1
55
0
4
Order By: Relevance
“…A recent study showed that the rectal swabs of 8 pediatric COVID-19 patients persistently tested positive after nasopharyngeal testing was negative, suggesting that the viral shedding from the GI tract might last longer than that from the respiratory tract [ 41 ]. In other cases, 3 COVID-19 patients with GI symptoms were re-admitted after pneumonia had resolved due to the persistence of intestinal SARS-CoV-2 infection [ 42 ]. Thus, our findings are in line with these clinical observations supporting the persistence of SARS-CoV-2 infection in the GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the rectal swabs of 8 pediatric COVID-19 patients persistently tested positive after nasopharyngeal testing was negative, suggesting that the viral shedding from the GI tract might last longer than that from the respiratory tract [ 41 ]. In other cases, 3 COVID-19 patients with GI symptoms were re-admitted after pneumonia had resolved due to the persistence of intestinal SARS-CoV-2 infection [ 42 ]. Thus, our findings are in line with these clinical observations supporting the persistence of SARS-CoV-2 infection in the GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Coronavirus can cause liver disorders and neurological symptoms, because those are the part of Coronaviridae family (33). Most of Covid19 positive sufferers got fever or respiratory problems (33)(34)(35)(36). Other symptoms and indication of Covid19 sufferers are cough, diarrhea, myalgia or fatigue, and headaches (35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the persistence of intestinal SARS-CoV-2 shedding in some patients has led to their re-admission after their pneumonia had resolved [4]. Antiviral therapies appear to be an important means to resolve the problem of viral persistence.…”
Section: Dear Editormentioning
confidence: 99%